2021
DOI: 10.1155/2021/2984470
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Parameters Using Response Surface Methodology to Develop a Novel Kefir-Like Functional Beverage from Cheese Whey Enriched with Myrtle Juice

Abstract: Whey, liquid wastewater from cheese production, is one of the sources of dietary protein and lactose that are still largely unused for human consumption. It is only in recent years that it has aroused the interest of industries and sought as a valuable raw material and thus represents an opportunity for the manufacture of new products. The manufacture of fermented whey drink requires the mixing of whey with fruit juice or an aromatic plant to improve its organoleptic properties and acceptability. Myrtle, an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
3
4
1
Order By: Relevance
“…pH and • Brix were determined at the beginning and end, observing a drop of both pH and • Brix for all treatments (result not shown). This fact indicates that in all treatments, the microbial population grows and has been observed by other researchers [32,53,54]. Furthermore, there is a positive Pearson correlation between the relative decrease in pH and • Brix with the values reached for LAB (r = 0.81) and yeast (r = 0.66) growth.…”
Section: Validation Of the Modelssupporting
confidence: 83%
See 4 more Smart Citations
“…pH and • Brix were determined at the beginning and end, observing a drop of both pH and • Brix for all treatments (result not shown). This fact indicates that in all treatments, the microbial population grows and has been observed by other researchers [32,53,54]. Furthermore, there is a positive Pearson correlation between the relative decrease in pH and • Brix with the values reached for LAB (r = 0.81) and yeast (r = 0.66) growth.…”
Section: Validation Of the Modelssupporting
confidence: 83%
“…Surprisingly, in two of the combinations ('OPT1' and 'OPT2'), where a better behavior was observed (with values of D = 0.8), there were those where only the WKG was used, even though in one of them ('OPT1'), the substrate mixture used contained >70% GMW. The LAB values achieved were 8-fold higher than those reported by Sabokbar and Khodaiyan [58] and 3.8-fold higher than those reported by M'Hir et al [32], while for yeasts, they were 2270-fold higher than those reported by Sabokbar and Khodaiyan [58], and 280-fold higher than those reported by M'Hir et al [32].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations